Automated Reasoning with Analytic Tableaux and Related Methods 22nd International Conference, TABLEAUX 2013, Nancy, France, September 16-19, 2013, Proceedings - Galmiche, Didier; Larchey-Wendling, Dominique (Lecture Notes in Artificial Intelligence,, 2013)
This book constitutes the refereed proceedings of the 22th International Conference on Automated Reasoning with Analytic Tableaux and Related Methods, TABLEAUX 2013, held in Nancy, France, in September 2013. The 20 revised research papers presented together with 4 system descriptions were carefully reviewed and selected from 38 submissions. The papers cover many topics as proof-theory in classical and non-classical logics, analytic tableaux for various logics, related techniques and concepts, e.g., model checking and BDDs, related methods (model elimination, sequent calculi, resolution, and connection method), new calculi and methods for theorem proving and verification in classical and non-classical logics, systems, tools, implementations and applications as well as automated deduction and formal methods applied to logic, mathematics, software development, protocol verification, and security.